PERAN PUSTAKAWAN SEBAGAI EDUKATOR DALAM LAYANAN PENELUSURAN INFORMASI DI PERPUSTAKAAN UNIVERSITAS TANJUNGPURA - Sarasawitri, Nada Auliya; Hanum, Atiqa Nur Latifa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe ineffective and time-consuming search of information in the library has caused many book collections being unused and it has been the researcherâ€™s concern in this study. This study aims to account the efforts and constraints of librarians in conducting their role as educators in information search service. The study was conducted using qualitative method, in which the discussion was presented descriptively. The data were collected through interviews, observation, and documentation to six informants. The findings show that the users are still confused in doing information search in the library. As the result, they must spend more time searching for the collection of books. This problem can be resolved by providing assistance to the users. Therefore, librarians as the educator take an important role in helping the users to find the relevant, correct, and accurate information independently. The constraints faced in providing library service are insufficient internet connection, limited facility, and lack of human resources.Â Keywords: Information Search, Library of Universitas Tanjungpura, Roles of Librarians.